NILAI RELIGIUS DALAM LEGENDA BATU JADI DAYAK BAKATI SEBIHAK DESA TAPEN KABUPATEN BENGKAYANG - Yuniyarti, Yuniyarti; Syam, Christanto; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe method used in this research was descriptive method and this research was in the form of qualitative. The approach used in this study was a structural approach. The techniques used in this research were observation, interview, record, and note technique. The results of this study were (1) Human relationship with God, that is, believes in the existence of God and believes that death is God's will. (2) Human's relationship with him/herself that is emotion, strong desire, honest, and curious. (3) Human relations with other human beings, namely trust, compassion, mutual giving, and cooperation / mutual cooperation. (4) Human relations with nature, namely nature provides a variety of human needs, humans need nature as a place to live, humans need nature as a shelter, and nature responds to human actions. (5) A plan for implementing the results of this research has been compiled in learning Indonesian in junior high school.Key words: Batu Jadi, Dayak Bakati Sebihak, Oral Literature, Religious Value